Find the quotient.
(4ab - 8a 2 + 12ac) ÷ 4a
b - 2a2 + 3c
b - 2a + 3c
abc

Question

Asked 11/14/2014 10:42:07 AM

Updated 11/15/2014 2:42:39 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/15/2014 2:42:39 AM]

s

cecil|Points 60|

Question

Asked 11/14/2014 10:42:07 AM

Updated 11/15/2014 2:42:39 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/15/2014 2:42:39 AM]

Rating

8

(4ab - 8a^2 + 12ac) ÷ 4a

= 4ab/4a - 8a^2/4a + 12ac/4a

= b - 2a +3c

= 4ab/4a - 8a^2/4a + 12ac/4a

= b - 2a +3c

Added 11/15/2014 2:41:37 AM

This answer has been confirmed as correct and helpful.

8

48j^5k^2 ÷ (-3j^3k)

= -16j^2k

= -16j^2k

Added 11/15/2014 2:42:32 AM

This answer has been confirmed as correct and helpful.

Find the greatest common factor of 15x 2 y 3 and -20x 3 yz.

Question

Not Answered

Updated 11/17/2014 9:09:13 PM

1 Answer/Comment

The greatest common factor of 15x^2y^3 and -20x^3yz is 5x^2y.

15x^2y^3 = 3*5x^2y^3

-20x^3yz = -4*5x^3yz

15x^2y^3 = 3*5x^2y^3

-20x^3yz = -4*5x^3yz

Added 11/17/2014 9:09:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 12:52:12 AM]

Divide 8y 7 ÷ 4y 5 **Weegy:** The result of (4y)^3/8y is 8y^2
**User:** find the right quotient.
36m 5 n 5 ÷ (12m 3) **Weegy:** 36m^5 n^5 ? (12m^3) = 3m^2 n^5 **User:** Find the quotient.
12 a3 p4 ÷ -2a2p
-6a3p5
-24ap3
-6ap3
6a5p3 **User:** Find the quotient.
4z a + 2 ÷ (-8z a - 2)
-z-4
-z
-z2a
-z4 (More)

Question

Not Answered

Updated 11/24/2014 12:29:05 AM

1 Answer/Comment

8y^7 ÷ 4y^5

= (8/4)*(y^7/y^5)

= 2*y^2

= 2y^2

= (8/4)*(y^7/y^5)

= 2*y^2

= 2y^2

Added 11/24/2014 12:28:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 12:54:47 AM]

Factor this expression completely : mr+ ns - nr - ms

Question

Updated 11/18/2014 10:13:57 PM

1 Answer/Comment

mr + ns - nr - ms

= mr - ms + n(s - r)

= m(r - s) + n(s - r)

= (r - s)( m - n)

= mr - ms + n(s - r)

= m(r - s) + n(s - r)

= (r - s)( m - n)

Added 11/18/2014 10:07:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 10:31:49 PM]

Factor 2x 2 - 10x + 8 completely.
2(x + 2)(x - 2)
2(x - 1)(x - 4)
2(x - 2)(x + 4) User: Factor 4b 2 - 9.
(4b + 3)(b - 3)
(2b + 3)(2b - 3)
(2b - 4)(2b - 5) User: How many terms are in the polynomial abcd + e - h 2?
two
three
five
six

Question

Not Answered

Updated 11/16/2014 9:48:53 PM

1 Answer/Comment

Simplify the expression.
3(2y - 8) - 2y(5 - y)
-2y 2 + 16y - 24
-5y - 8
2y 2 - 4y - 24
2y 2 + 16y - 24 **Weegy:** 3(2y - 8) - 2y(5 - y) = 6y - 24 - 10y + 2y^2 = 2y^2 - 4y - 24 **User:** Find the product.
(n + 7)(n - 2)
n² - 5n - 14
n² + 5n - 14
n² - 5n + 14 (More)

Question

Not Answered

Updated 11/15/2014 2:30:08 AM

1 Answer/Comment

(n + 7)(n - 2)

= n^2 + 7n - 2n - 14

= n^2 + 5n - 14

= n^2 + 7n - 2n - 14

= n^2 + 5n - 14

Added 11/15/2014 2:20:41 AM

This answer has been confirmed as correct and helpful.

34,459,744

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 723 [Total 6596] Ratings 14 Comments 583 Invitations 0 Offline

There are no comments.